ANALISIS PENDAPATAN USAHATANI WORTEL ORGANIK DAN NON ORGANIK DI DESA KUMELEMBUAI KECAMATAN TOMOHON TIMUR KOTA TOMOHON - Rivaldo Mathew Tangkawarow; Oktavianus ., Porajouw; Melsje Yellie Memah (Sam Ratulangi University, 2021)
This study aims to describe the income of organic carrots and non-organic carrots farming in Kumelembuai Village, East Tomohon District, Tomohon City. This study was conducted in May 2021. By using purposive and using primary and secondary data. So getting the respondents as many as 60 people were divided into 20 farmers organic carrots and 40 farmers of non-organic carrots. Based on the research results can be seen that the carrot farm income organic amounting to Rp. 22,686,838 and non-organic carrot farming income of Rp. 53,195,359. So it can be concluded that the income of organic carrot farming is smaller than that of non-organic carrot farming. Suggestions that can be given by researchers are that organic carrot farming can use manure or other organic fertilizers to increase their production, especially income.